Effect of chemical substitution on the construction of boroxine-based supramolecular crystalline polymers featuring B←N dative bonds. Issue 9 (8th February 2022) - Bhandary, Subhrajyoti; Shukla, Rahul; Van Hecke, Kristof
Abstract : B←N dative bond-associated molecular to polymeric crystals have been synthesized by tuning their electronic features. The supramolecular and quantum crystallographic aspects of the B←N dative bonds were thoroughly investigated. Abstract : We report the mechanochemical synthesis of five single-crystalline phenylboroxine and 1, 4-diazabicyclo[2.2.2]octane (DABCO) ligand-based adducts, directed by boron–nitrogen dative bonds. By tuning the electronic features of the phenylboroxines by chemical modifications (–H/–OMe/–F/–Cl/–Br) at the para -position, the formation of the resulting bicomponent adducts can be controlled to obtain molecular to 1D polymeric crystalline materials. The electrostatic and quantum topological aspects of the B←N bonds reveal the origin for the different binding modes of the boroxine–DABCO adducts yielding molecular to polymeric structures.